Essential Oil Composition and Antioxidant Activity of Paramignya lobata (SCOPUS) - Wan Mohd Nuzul Hakimi Wan Salleh (Tanjung Malim, 2021)
Essential Oil Composition and Antioxidant Activity of Paramignya lobata (SCOPUS) by Wan Mohd Nuzul Hakimi Wan Salleh